Public realm as city welfare & citizens wellbeing: the case of Cao Yang – Shanghai - Tosi, Maria Chiara; Turvani, Margherita E.; Muna Rin, Stefano (Journal of Architecture and Urbanism, 2017)
This paper discusses how the improvement of the quality of collective and public spaces can positively affect the wellbeing of the citizens and the welfare of the city, using as a demonstration site Cao Yang New Village, one of the first planned urban development for workers in Shanghai, China, designed and built during the Fifties of the past century, just few years later Mao Zedong proclaimed the establishment of the People’s Republic of China, on October 1, 1949.The paper shows how, by careful design interventions, the enhancement of the connectivity and of the porosity in the neighbourhood gives rise to an easier accessibility for citizens, especially for children, mothers, elderly, and people with disabilities, allowing them to get to schools, parks, sport facilities, public offices and other collective spaces, therefore improving their wellbeing.By detailed and careful design, appropriate urban policies in Chinese cities can help to respond to the citizens increasing demand for public space. Our work suggests that a similar approach should be included in many cities agenda in China, to align to the China’s New Urbanization Plan 2014–2020 that focuses on sustainable growth, improved people’s living conditions and a clearer cultural identity.